Snake venomics of the Siamese Russell's viper (Daboia russelli siamensis) - Relation to pharmacological activities - Risch, Michaela; Georgieva, Dessislava; von Bergen, Martin; Jehmlich, Nico; Genov, Nicolay; Arni, Raghuvir K. [UNESP]; Betzel, Christian (Elsevier B.V., 2009)
The venom proteome of Daboia russelli siamensis, a snake of medical importance in several Asian countries, was analysed by 2-D electrophoresis, subsequent MS/MS and enzymatic assays. The proteome comprises toxins from six protein families: serine proteinases, metalloproteinases, phospholipases A(2), L-amino acid oxidases, vascular endothelial growth factors and C-type lectin-like proteins. The venom toxin composition correlates with the clinical manifestation of the Russell's viper bite and explains pathological effects of the venom such as coagulopathy, oedema, hypotensive, necrotic and tissue damaging effects. The vast majority of toxins are potentially involved in coagulopathy and neurotoxic effects. The predominant venom components are proteinases capable of activating blood coagulation factors and promoting a rapid clotting of the blood, and neurotoxic phospholipase A(2)s. The analysis of the venom protein composition provides a catalogue of secreted toxins. The proteome of D. r. siamensis exhibits a lower level of toxin diversity than the proteomes of other viperid snakes. In comparison to the venoms of Vipera ammodytes ammodytes and Vipera ammodytes meridionalis, the venom from D. r. siamensis showed quantitative differences in the proteolytic, phospholipase A2, L-amino acid oxidase and alkaline phosphatase activities. (c) 2009 Published by Elsevier B.V.
Keywords: Proteome; Snake venom; Protein family; Daboia russelli siamensis; 2-D electrophoresis